Metagenomic detection and biochemical characterization of a Streptomyces tyrosinase from Mesopotamian marsh soils: Implications for phenolic turnover - Altaee, Nadia; Mahdi, Oras Abdulsayed; Sadeq, Farah Mohammed Saeed (Indonesian Journal of Biotechnology, 2025)
Wetland soils in southern Iraq store large carbon pools and contain abundant phenolics that can modulate microbial decomposition. In this study, we investigate bacterial tyrosinases (TYRs), type III copper enzymes that oxidize mono‐ and diphenols, in Mesopotamian marsh soils using a combined metagenomic and biochemical approach. Degenerate primers targeting conserved CuA/CuB motifs recovered diverse partial tyr fragments affiliated with Proteobacteria and Actinobacteria. From one sample, we amplified the full melC operon from a Streptomyces lineage; expressed the tyrosinase in E. coli; and purified the enzyme (SZTYR). SZTYR displayed an alkaline pH optimum (~9); retained activity up to ~70 °C; and preferentially oxidized diphenols (e.g., L‐DOPA, dopamine) over monophenols. The enzyme also acted on phenolics relevant to peat/wetland matrices (e.g., caffeic, protocatechuic, p‐coumaric and gallic acids). The results document TYR genetic diversity in Iraqi marsh soils and establish the biochemical profile of an alkaline‐adapted Streptomyces tyrosinase. While ecosystem‐level impacts were not measured, our findings motivate field‐scale assessments of in situ TYR activity, phenolic pools and oxygen/pH dynamics to evaluate potential consequences for phenolic turnover and carbon cycling in aridifying wetlands.